Spatial and temporal characteristics of carbon emission and sequestration of terrestrial ecosystems and their driving factors in mainland China—a case study of 352 prefectural administrative districts - Lin, Jingyuan; Guo, Yi; Li, Jiayan; Shao, Ming; Yao, Peng (Frontiers in Ecology and Evolution, 2023)
Global climate change, increase in human activities, and prominence of ecological issues have led to uneven quantitative and spatial distributions of carbon emission and sequestration of terrestrial ecosystems. Such uneven distributions can lead to more negative impacts on the natural environment and human living conditions. From 2000 to 2017, carbon emission and sequestration of terrestrial ecosystems showed annual rising trends but with an increasing difference in growth. Carbon emission presents the distribution characteristics of "high in the east and low in the west". The overall spatial distribution features of Carbon sequestration are "high in the east and low in the west, and low in the south and low in the north". And their spatial distribution shows positive correlation and aggregation. Therefore,based on the carbon neutralization policy, we conducted geographically weighted regression (GWR) modeling to analyze and determine the key influencing factors of China and their spatial distribution for carbon emission and sequestration of terrestrial ecosystems. Our results showed that total population (TP), per capita gross domestic product (GDP) (PCG), proportion of secondary industry output (PSIO), scale of urban built-up area (SUB), green space proportion in city areas (GSP), normalized difference vegetation index (NDVI), and temperature (TEM) are factors driving carbon sequestration and carbon emission. We found that different levels of socioeconomic development and natural climate conditions contributed to the differences between groups. Based on these results, we further divided the Chinese cities into 6 groups. Groups 1, 2, 3, and 6 are areas where carbon emission and sequestration are governed by both socioeconomic and natural ecological factors. Group 4 represents areas where carbon emission and sequestration are majorly impacted by PCG and SUB, thereby rendering socioeconomic factors as the major driving forces. Group 5 represents areas where carbon emission and sequestration are sensitive to the natural environment, with GSP and NDVI being the driving factors. Considering the uneven distribution of carbon sequestration and emission and the diverse driving factors in different areas of China, we provided guidance for future environmental policies aimed at reducing the uneven distribution of carbon sequestration and emission in different areas to achieve carbon neutralization.